Direct deliberative democracy : how citizens can rule - Campbell, Debra J.; Crittenden, Jack (Black Rose Books, 2019)
"Campbell and Crittenden show why citizens should make laws directly and how citizens can do so through democratic deliberation. With money, lobbyists, and corporations dominating local, state, and national elections, now is the time for citizens to take control of all aspects of their lives, both public and private, by deliberating together to make the laws and rules by which we live."--